Statično iskorištenje prijevoznih kapaciteta u prigradskom putničkom cestovnom prometu - Rajsman, Marijan (Promet - Traffic&Transportation, 2012)
A large sample of departures of a service operated by a transport company in public suburban passenger road traffic has been used for the study of random variable CJp expressed by the average number of passengers carried per stop-to-stop sections of the suburban route, as one of the essential bus utilization and output indices. Depending upon the system of scheduled departures, the mean value of variable CJp has been obtained which for departures in a workday is 17 passengers per a stop-to-stop section of the route and 7 passengers for departures on Saturdays. The obtained mean values of the observed variable make it possible for us to compute the coefficient of static utilization of transport capacities, i.e. the average utilization rate of bus transport capacities on suburban lines: 21% on workdays, 14% on Saturdays, 9% on Sundays. It has been established that variable CJp adopts its values by the exponential law of probability, i.e. the values from the sample originate from the basic array of exponential distribution. Test.ing the difference between the arithmetic means of the examples of variable CJp depending upon the system of departures maintained, has yielded a statistically significant difference and at the same time confirmed the justifiability of the applied variable analysis methods.